Helical TomoTherapy for locally advanced or recurrent breast cancer. Issue 1 (December 2017) - Duma, M.; Heinrich, C.; Schönknecht, C.; Chizzali, B.; Mayinger, M.; Devecka, M.; Kampfer, S.; Combs, S.
Abstract Purpose We report our experience of using helical tomotherapy (HT) to treat large and irregular shaped loco-regional advanced breast cancer target volumes embracing various organs at risk. Patients and methods We retrospectively analyzed 26 patients treated for very large, irregular shaped breast cancers. Patients were treated either with the intent to achieve local control in a primary setting (n  = 14) or in a reirradiation setting (n  = 12). The recurrence group was heavily pretreated with systemic therapy. Tumors were characterized by wide infiltration of the skin, encompassing mostly a complete hemithorax. The primary group underwent irradiation of supraclavicular, infraclavicular, axillary and parasternal lymphonodal region. Radiotherapy was combined with chemotherapy (n  = 11). We assessed the PTV volume and its craniocaudal extension, the dose to the organs at risk, acute toxicity and survival. Results Median PTV was 2276 cm3 (1476–6837 cm3 ) with a median cranio-caudal extension of 28 cm (15–52 cm). The median dose to PTV was 40 Gy (32–60Gy). HT could be carried out in all patients without interruption. The acute toxicities were mild to moderate. The median LRFS and OS after radiotherapy was 21 and 57 months for the primary group versus 10 and 11 months for the recurrence group. Median PFS was 18 months (primary group) and 7 months (recurrence group). Conclusions HT is feasible for advanced thorax embracing target volumes with acceptable acute toxicity. Both curative and palliative indications can be considered good indications based on treatment volume and anatomical constellation.